Covid19 and World Tourism Research - I Nyoman Sudapet; Ronny Durrotun Nasihien; Mohd Haziman Wan Ibrahim; Muhammad Ikhsan Setiawan; Agus Sukoco; Amrun Rosyid (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Constructs and visualizes bibliometric networks research in Covid19 and world tourism research with meta-analysis techniques using VOS-viewer analysis. Design/methodology/approach: This research is a bibliometric analysis, a statistical evaluation of published books, or the chapters of a book, scientific articles in COVID19, and tourism field, also it is an effectual way to measure the influence of publication in the scientific community. First analysis using Scopus.com analysis search result, COVID19 and tourism research publication, Next analysis using VOS-viewer, a software tool for constructing and visualizing bibliometric networks in COVID19, and tourism field. Findings: Based on VOS-viewer analysis using COVID19 and tourism research publication, 2020-2021, 303 document results, in scopus.com. COVID19 and tourism research publication, 2020-2021, 303 document results, scopus.com, best 3 affiliations are Texas A&M University, The University of Sydney, and Griffith University; best 3 countries and territories are United Kingdom, United States, and Australia; best 3 funding sponsor are National Natural Science Foundation of China, European Commission, and European Research Council. Paper type: Research Paper